Chlamydophila psittaci pneumonia followed by lower gastrointestinal ischemic necrosis: a case report - Shifeng Shao; Jun Liu; Zhenbing Wu; Shasha Wu (Frontiers in Medicine)
BackgroundPsittacosis, also known as parrot fever, is an uncommon infectious disease caused by Chlamydophila psittaci (C. psittaci). While C. psittaci infections are usually not life-threatening, the pathogenesis and associated complications are not yet fully understood.Case descriptionA 54-year-old male was hospitalized due to a cough, accompanied by expectoration and dyspnea. After admission, the patient's breathing rapidly deteriorated, and despite the use of a ventilator, it was challenging to maintain respiratory function. While initiating extracorporeal membrane oxygenation (ECMO) and empirical anti-infection treatments, the alveolar lavage fluid was collected and examined by metagenomics next generation sequencing (mNGS). The mNGS result indicated C. psittaci. Subsequently, the anti-infection regimen was immediately adjusted. The respiratory function improved on the 13th day after admission, and ECMO was withdrawn. However, the patient developed abdominal distension and intestinal edema. After intravenous infusion therapy, intestinal ischemia and necrosis occurred and surgical resection was performed. The patient's condition improved after the operation and he was transferred to a local hospital for rehabilitation.ConclusionThis case report demonstrates the development of intestinal ischemic necrosis following severe C. psittaci pneumonia. This unique association has not been reported previously and highlights the importance of potential gastrointestinal complications in severe C. psittaci pneumonia, which are often underestimated. Timely diagnoses and treatments of such infections and complications are necessary to achieve favorable clinical outcomes.